Still waters [large type] - Goldman, Matt, 1962- (Thorndike Press large print mystery series., 2025)
"Liv and Gabe Ahlstrom are estranged siblings who haven't seen each other in years, but that's about to change when they receive a rare call from their older brother's wife. "Mack is dead," she says. "He died of a seizure." Five minutes after they hang up, Liv and Gabe each receive a scheduled email from their dead brother, claiming that he was murdered. The siblings return to their family-run resort in the Northwoods of Minnesota to investigate Mack's claims, but Leech Lake has more in store for them than either could imagine. Drawn into a tangled web of lies and betrayal that spans decades, they put their lives on the line to unravel the truth about their brother, their parents, themselves, and the small town in which they grew up. After all, no one can keep a secret in a small town, but someone in Leech Lake is willing to kill for the truth to stay buried"--Page [4] of cover.